Proposed marketing strategy for fixed mobile convergence products case study: Telkomsel One - Edwina Edwina; Harimukti Wandebori (Global Academy of Multidisciplinary Studies, 2024)
Purpose: This study aims to determine proposed business and marketing strategy including segmenting, targeting & positioning (STP) and marketing mix (7P) for Telkomsel One Method: This study combined qualitative and quantitative research by distributing questionnaires directly to 253 respondents. A non-probability sampling technique was used. The primary data source in this research was obtained directly from questionnaire respondents. The method used SPSS version 23. Results: The research results based on the cluster analysis show that there are three distinct segments of Telkomsel One: budget-conscious users, convenience seekers, and tech enthusiasts. The results of the analysis become the basis for new segmentation, targeting, and positioning strategies for Telkomsel One. Strategies encompass adjusting product lines and pricing, conducting several promotions and strategic partnerships, using omnichannel approaches, frontliner skills training, streamlining processes, and integrating IT Tools to deliver excellent service to customers. Conclusions: The study concludes that effective implementation of STP and the marketing mix (7P) enhances Telkomsel One’s ability to meet diverse customer needs while maintaining competitiveness in the rapidly evolving telecommunications market. Limitations: This study is limited by its reliance on non-probability sampling, which may affect generalizability. Additionally, the research only focused on respondents in a specific context, limiting the broader market representation. Contribution: This research offers a practical framework for telecommunications companies to apply integrated marketing strategies in the era of fixed-mobile convergence, ensuring long-term customer satisfaction and business sustainability.